Pengaruh Self-Efficacy, Technology Acceptance, dan Motivasi Belajar Terhadap Prestasi Akademis Siswa dalam Online Learning di SMPK Kalam Kudus Dumai - Esther Juli Anggia Sihombing; Pujianto Yugopuspito (Journal on Education, 2023)
The use of e-learning in accelerated learning due to the Covid-19 pandemic has brought about changes in the world of education in Indonesia so that it has an impact on student academic achievement. Students' academic achievement is influenced by several factors, including self-efficacy, technology acceptance, and learning motivation. This study aims to determine the effect of self-efficacy, technology acceptance, and learning motivation on students' academic achievement in online learning. The research subjects were 38 students of SMPK Kalam Kudus Dumai, where among students there was a decrease in academic achievement in online learning. The study used a quantitative approach with correlation and regression testing. The results obtained show that self-efficacy, technology acceptance, and learning motivation together have a positive effect on students' academic achievement in online learning.